2011
DOI: 10.3109/10903127.2011.569848
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Defibrillation or Defibrillation After Cardiopulmonary Resuscitation

Abstract: Objectives. This study aimed to determine whether short cardiopulmonary resuscitation (CPR) by emergency medical services before defibrillation (CPR first) has a better outcome than immediate defibrillation followed by CPR (shock first) in patients with ventricular fibrillation/pulseless ventricular tachycardia (VF/pulseless VT) out-of-hospital cardiac arrest. Methods. We analyzed a national database between 2006 and 2008, and included patients aged 18 years or more who had witnessed cardiac arrests and whose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 19 publications
(25 reference statements)
0
4
0
Order By: Relevance
“…However, we have to keep in mind that this, and a large before-after study from Seattle 243 that showed better outcomes with 90 s of CPR before a shock when the response interval was >4 min), are from a time when 3 stacked-shocks were used and shorter periods of CPR between shocks (1 min). Evidence from five RCTs 242,[244][245][246][247] and another study 248 suggests that among unmonitored patients with OHCA and an initial rhythm of VF/pVT, there is no benefit in a period of CPR of 90-180 s before defibrillation when compared with immediate defibrillation with CPR being performed while the defibrillator equipment is being applied.…”
Section: Cpr Versus Defibrillation First For Out-of-hospital Cardiac Arrestmentioning
confidence: 99%
“…However, we have to keep in mind that this, and a large before-after study from Seattle 243 that showed better outcomes with 90 s of CPR before a shock when the response interval was >4 min), are from a time when 3 stacked-shocks were used and shorter periods of CPR between shocks (1 min). Evidence from five RCTs 242,[244][245][246][247] and another study 248 suggests that among unmonitored patients with OHCA and an initial rhythm of VF/pVT, there is no benefit in a period of CPR of 90-180 s before defibrillation when compared with immediate defibrillation with CPR being performed while the defibrillator equipment is being applied.…”
Section: Cpr Versus Defibrillation First For Out-of-hospital Cardiac Arrestmentioning
confidence: 99%
“…Although patients with VF as an initial rhythm were more likely to be successfully resuscitated than with other rhythms, the less than 30% survival rate remains unsatisfactory ( Rajan et al, 2017 ). Survival from OHCA depends on a complex system working together to secure the best outcome, and early defibrillation with concurrent high-quality cardiopulmonary resuscitation (CPR) is the most important life-saving intervention for VF ( Koike et al, 2011 ). To provide a general treatment strategy, the latest guidelines for CPR and emergency cardiovascular care recommend the initiation of high-quality CPR, delivery of an electrical shock as soon as a defibrillator is available and every 2 min thereafter if VF persists ( Panchal et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…18 Since October 2006, CPR has been based on the respective 2005 guidelines. 13,19 Do-not-resuscitate orders or living wills are not generally accepted, and EMS personnel are not allowed to terminate or withhold resuscitation out of hospital. Therefore, most patients who have an OHCA who are treated by EMS personnel are transported to hospital, excluding those with decapitation, incineration, decomposition, rigor mortis, or dependent cyanosis.…”
Section: Ems System In Japanmentioning
confidence: 99%